Efficient noise averaging in color holography by integration on shifted Fourier spectra - Ducin, Izabela; Kakarenko, Karol; Makowski, Michał; Kowalczyk, Adam; Bieda, Marcin; Suszek, Jarosław (Photonics Letters of Poland, 2014)
Modern holography is dealing mainly with the speckle noise and computational complexity. Reaching a compromise between the computational complexity (computing time) and quality of obtained images is required. This leads to a need to obtain a simple method of noise suppression with low computation complexity. An improved efficient projection of color images is presented. It uses a time averaging of intensity patterns reconstructed from the same Fourier hologram with lateral shifting in x and y direction. We try to establish the optimal step of shifting the Fourier spectra in both directions for each of the primary colors. Full Text: PDF References M. Makowski, "Minimized speckle noise in lens-less holographic projection by pixel separation," Opt. Express 21, 29205-29216 (2013). CrossRef M. Makowski, A. Siemion, I. Ducin, K. Kakarenko, M. Sypek, A.M Siemion, J. Suszek, D. Wojnowski, Z. Jaroszewicz, A. Kolodziejczyk, "Complex light modulation for lensless image projection", Chin. Opt. Lett. 9, 120008 (2011). CrossRef L. Golan and S. Shoham, "Speckle elimination using shift-averaging in high-rate holographic projection," Opt. Express 17, 1330-1339 (2009) CrossRef R. W. Gerchberg, and W. O. Saxton, "A practical algorithm for the determination of phase from image and diffraction plane pictures", Optik (Stuttg.) 35, 237–246 (1972). A. Czerwiński, K. Kakarenko, M. Sypek, M. Makowski, I. Ducin, J. Suszek, A. Kolodziejczyk, J. Bomba, "Modeling of the optical system illuminated by quasi-monochromatic spatially incoherent light: New numerical approach", Opt. Letters 37, 4723-4 (2012). CrossRef T. Shimobaba, T. Ito, N. Masuda, Y. Ichihashi, and N. Takada, "Fast calculation of computer-generated-hologram on AMD HD5000 series GPU and OpenCL," Opt. Express 18, 9955-9960 (2010). CrossRef T. Shimobaba, Y. Sato, J. Miura, M. Takenouchi, and T. Ito, "Real-time digital holographic microscopy using the graphic processing unit," Opt. Express 16, 11776-11781 (2008). CrossRef